The Influence of Social Media Use on the Cognitive Abilities of Fifth Grade Students in Science Subjects at SDN 4 Abuan - Putra, I Ketut Dedi Agung Susanto; Luh Candra Mitha Utami (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of the application of social media on the cognitive abilities of students in science class V SDN 4 Abuan. This type of research uses quantitative descriptive research with data collection techniques using observation and tests. The population of this study is all students of SDN 4 Abuan odd semester of the 2022/2023 academic year. As a sample in this study, there were 15 grade V students of SDN 4 Abuan in the odd semester of the 2022/2023 academic year. Based on the results of data analysis, it was found that there was a significant influence on the use of social media in learning. The effective time for learning by utilizing social media is as much as 25% of learning and 1 to 3 hours during the learning process both at school and at home